Mechanical properties and damping capacity of polypropylene fiber reinforced concrete modified by rubber powder. (10th May 2020) - Mo, Jinxu; Zeng, Lei; Liu, Yanhua; Ma, Linling; Liu, Changjun; Xiang, Sheng; Cheng, Guoyuan
Highlights: The rubber powder is added into the polypropylene fiber concrete as the damping unit. The effect of rubber powder on the mechanical properties of PFRC was discussed. DIC technique was used to monitor full field strain and crack development. Damage damping capacity, stiffness degradation and energy dissipation quantified. Abstract: In this paper, the effects of rubber powder on mechanical properties and damping capacity of polypropylene fiber reinforced concrete (PFRC) were explored. Axial compression tests were carried out on concrete cubes and prisms, and the digital image correlation (DIC) technique were employed to monitor the full field strain and track the crack development of concrete specimens. Free vibration tests were carried out on ten cantilever beams specimens under various damage levels. Bending properties and damping characteristics of the beams were investigated. The experimental results show that the addition of rubber powder improves the damping capacity of PFRC while reducing compressive strength of the concrete and increasing the peak strain. The degradation rate of the bending dynamic stiffness of PFRC beams slows down with the increase of polypropylene fiber content, and accelerates with the addition of rubber powder. Meanwhile, the crack development path and strain distribution of prism specimens are analyzed accurately by using DIC technology.